Modifikasi Nori Rumput Laut Ulva Lactuca Dengan Konsentrasi Carboxylmethyl Cellulose (CMC) Yang Berbeda - Kolo, Yuliana; Henggu, Krisman Umbu; Luik, Renfred; Benu, Marlo J.R; Manteu, Shindy Hamidah (Jambura Fish Processing Journal, 2025)
Ulva lactuca is a type of seaweed that grows in the coastal areas of East Sumba Regency and its use is still limited. One of the efforts made to increase its economic value is to use it as a raw material for nori. Nori made from seaweed has disadvantages such as not being elastic, easily tearing and cracking. Therefore, it is necessary to add Carboxylmethyl cellulose (CMC) which functions as an emulsifier and stabilizer so that it can reduce surface tension so that the resulting nori has good elasticity, does not crack or tear. The CMC concentrations used in this research were 1%, 3%, 5%. The research results showed that Ulva lactuca nori without CMC treatment (P0) had a fairly high crack or tear size, reaching 97.23 mm. In contrast, cracks were not identified in nori products treated with 5% CMC (P3). The proximate composition of Ulva lactuca seaweed nori with different CMC concentrations obtained an average value of water content ranging from 17.49%-30.69%, ash content 10.55%-14.55%, fat content 0.65%-3 .94%, protein content 2.12%-3.04% and carbohydrate content 48.87%-61.89%. Based on the results of statistical analysis, the use of different CMC concentrations had a significant effect (P0.05) on water content, ash content, fat content, protein and carbohydrate content. Optimization of the resulting nori was obtained using 5% CMC (P3) treatment, this is because the physical characteristics of the nori produced have a good level of elasticity (no cracks or tears), have a water content of 30.69%, ash 10.55%, lipid 0 .65%, protein 2.65% and carbohydrates 55.44%.